The Comparative Economics of Catch-Up in Output per worker, total factor productivity and technological gain in Sub-Saharan Africa - John Ssozi; Simplice A. Asongu (African Governance and Development Institute (AGDI), 2015)
After investigating the effect of external financial flows on total factor productivity and technological gain, we use the beta catch-up and sigma convergence to compare dispersions in output per worker, total factor productivity and technological gain in Sub-Saharan Africa (SSA) for the years 1980-2010. The comparative evidence is articulated with income levels, years of schooling, and health factors. We find; first, a positive association between foreign direct investment, trade openness, foreign aid, remittances and total factor productivity. However, when foreign direct investment is interacted with schooling, it is direct effect becomes negative on total factor productivity. Second, beta catch-up is between19.22% and 19.70% per annum with corresponding time to full catch-up of 25.38 years and 26.01 years respectively. Third, we find sigma-convergence among low-income nations and upper-middle income nations separately, but not for the entire sample together. Fourth, schooling in SSA is not yet a significant source of technology, but it can make external financial inflows more effective. Policies to induce external financial flows are not enough for development if absorptive capacity is low. More policy implications are discussed.
Keywords: E23; F21; O11; O33; O55; 330; External capital flows; Human capital; Total Factor Productivity; Convergence; and Sub-Saharan Africa